Common Features and Traits of Education Reform in the Republic of Kazakhstan and People’s Republic of China (Journal of Educational Sciences, 2017)
The article analyzes the process of reforming the education system in the two rapidly developing countries – Kazakhstan and China, through the lens of transformation of secondary-level education; it discusses similarities and differences in the process. It raises issues related to safety of secondary education restructuring, which largely determines spiritual and moral foundations of a developing identity of a modern school student, their creativity, mobility, and ability to deal with numerous problems in life on their own. The authors used a comparative methodof analysis of scientific literature on this matter and provided empirical data from a survey conducted among school students in Kazakhstan and China. Peoples Republic of China has managed to pass important miles ones in the reform of its education system without losing socially significant cultural and spiritual referencepoints of the country, which deserves careful study and consideration in practical reforming activities of any country. What is important is the fact that there is a general strategic focus of education development of the two countries, which suggests maintaining positive socio-cultural experience that provided in the past and still provides an indispensable potential for advanced education. It brings together two countries that are undergoing modernization and lays groundwork for long-term cooperation in the field of education.
Keywords: reforming education; secondary education; didactic problems; traditions in school education; educational process; quality of education; teacher’s status; cultural and moral characteristics of an individual